On melting of boron subnitride B₁₃N₂ under pressure - Solozhenko, V.L.; Mukhanov, V.A. (Сверхтвердые материалы, 2017)
Melting of rhombohedral boron subnitride B₁₃N₂has been studied in situ at pressures to 8 GPa using synchrotron X-ray diffraction and electrical resistivity measurements. It has been found that above 2.6 GPa B₁₃N₂melts incongruently, and the melting curve exhibits positive slope of 31(3) K/GPa that points to a lower density of the melt as compared to the solid phase.